Upon further review : the greatest what-ifs in sports history - Pesca, Mike (2018)
"From Mike Pesca, host of the popular Slate podcast The Gist, comes the greatest sports minds imagining how the world would change if a play, trade, injury, or referee's call had just gone the other way. No announcer ever proclaimed: "Up Rises Frazier!" "Havlicek commits the foul, trying to steal the ball!" or "The Giants Lose the Pennant, The Giants Lose The Pennant!" Such moments are indelibly etched upon the mind of every sports fan. Or rather, they would be, had they happened. Sports are notoriously games of inches, and when we conjure the thought of certain athletes - like Bill Buckner or Scott Norwood - we can't help but apply a mental tape measure to the highlight reels of our minds. Players, coaches, and of course fans, obsess on the play when they ask, "What if?" Upon Further Review is the first book to answer that question. Upon Further Review is a book of counterfactual sporting scenarios. In its pages the reader will find expertly reported histories, where one small event is flipped on its head, and the resulting ripples are carefully documented, the likes of... What if the U.S. Boycotted Hitler's Olympics? What if Bobby Riggs beat Billie Jean King? What if Bucky Dent popped out at the foot of the Green Monster? What if Drew Bledsoe never got hurt? Upon Further Review takes classic arguments conducted over pints in a pub and places them in the hands of dozens of writers, athletes, and historians. From turning points that every sports fan rues or celebrates, to the forgotten would-be inflection points that defined sports, Upon Further Review answers age old questions, and settles the score, even if the score bounced off the crossbar"--
Foreword / by Malcolm Gladwell -- Introduction / by Mike Pesca -- What if Muhammad Ali had gotten his draft deferment? / by Leigh Montville -- What if football had been deemed too boring in 1899? / by Jason Gay -- What if the United States had boycotted Hitler's Olympics? / by Shira Springer -- What if the 2017 Golden State Warriors traveled through time to play the greatest teams in NBA history? / by Ethan Sherwood Strauss -- What if horse racing was still the most popular sport in America? / by Peter Thomas Fornatale -- What if I hadn't written that fan letter to Dan Majerle in April 1993? / by Jesse Eisenberg -- What if Wayne Gretzky hadn't been an Oiler? / by Katie Baker -- What if Major League Baseball had started testing for steroids in 1991? / by Ben Lindbergh -- What if Bucky Dent hadn't homered over the Green Monster in 1978? / by Stefan Fatsis -- What if Jerry Tarkanian had beaten the NCAA and liberated college basketball? / by Jonathan Hock -- What if football were reinvented today? / by Nate Jackson -- What if there had always been sports PR flacks? / by L. Jon Wertheim -- What if...Title IX never was? / by Mary Pilon -- What if Tom Brady hadn't stepped in/taken over for an injured Drew Bledsoe? / by Steve Kornacki -- What if the 1999 U.S. Women's National Soccer Team had lost the Women's World Cup? / by Louisa Thomas -- What if the Olympics had never dropped tug-of-war? / by Nate DiMeo -- What if Billie Jean King had lost to Bobby Riggs? / by Wayne Coffey -- What if Mike Tyson had beaten Buster Douglas? / by Jeremy Schaap -- What if? A tour through NBA injury history / by Neil Paine ; with introductory notes on the topic "What if Bernard King hadn't been injured? / by Mike Pesca -- What if the Dodgers had left Brooklyn? / by Robert Siegel -- What if a blimp full of money had exploded over World Track Headquarters in 1952? / by Paul Snyder -- What if baseball teams only played once a week? / by Will Leitch -- What if Bobby Fischer had received proper psychiatric help? / by Dylan Loeb McClain -- What if basketball rims were smaller than basketballs? / by Jon Bois -- What if the AFL-NFL merger had been complicated by the Jets' loss in Super Bowl III? / by Michael MacCambridge -- What if the National League had the DH? / by Rob Neyer -- What if Nixon had been good at football? / by Julian E. Zelizer -- What if Bill Walton had healthy knees? / by Bob Ryan -- What if Roger Bannister trained today? / by Liam Boylan-Pratt -- What if Nat "Sweetwater" Clifton's pass hadn't gone awry? / by Claude Johnson -- What if Game 7 of the 2016 World Series had turned into every sports movie ever made? / by Josh Levin
Includes bibliographical references (pages [287]-289) and index
Keywords: Sports -- Anecdotes; Sports -- Miscellanea; Trivia and miscellanea; Anecdotes; Miscellanea; Counterfactual histories; Anecdotes; Trivia and miscellanea